2004
DOI: 10.1021/jp036287e
|View full text |Cite
|
Sign up to set email alerts
|

How Solvents Affect Acetaminophen Etching Pattern Formation:  Interaction between Solvent and Acetaminophen at the Solid/Liquid Interface

Abstract: The objective of this work was to further elucidate the dissolution process of acetaminophen crystals at the molecular level. The differences in the etching patterns from different solvents were used to study the interactions between solvent and acetaminophen molecules at the solid−liquid interface, such as solubilizing ability and potential solvent adsorption. The predicted etching patterns, based on the projections of attachment energies on the corresponding faces together with the solubilizing ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 30 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…Therefore the effects of polymeric additives on the dissolution of FFA cocrystals are attributed to surface adsorption of the polymers through specific interactions with the crystal surface, in particular, hydrogen bonding. [17][18][19][20]23,26,38,39 Among the polymers used in this study, PEG, containing a high percentage of hydrogen acceptors in the backbone, is the most hydrophilic, while PVP-VA, containing 40% acetate side chains in comparison to PVP, is the most hydrophobic. 11 Based on the dissolution experiment of the single FFA I crystal, the FFA I (100) face is more hydrophobic because it has a slower face dissolution rate in Figure 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 COs were the only solid phase in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the effects of polymeric additives on the dissolution of FFA cocrystals are attributed to surface adsorption of the polymers through specific interactions with the crystal surface, in particular, hydrogen bonding. [17][18][19][20]23,26,38,39 Among the polymers used in this study, PEG, containing a high percentage of hydrogen acceptors in the backbone, is the most hydrophilic, while PVP-VA, containing 40% acetate side chains in comparison to PVP, is the most hydrophobic. 11 Based on the dissolution experiment of the single FFA I crystal, the FFA I (100) face is more hydrophobic because it has a slower face dissolution rate in Figure 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 COs were the only solid phase in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] When a polymer is present in solution, the polymer molecules can also be adsorbed on the surface of the dissolving crystal to form an adsorption layer, which affects solute bulk diffusion as well as surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study also showed that dissolution process has direction preference like crystallization process (3,20,26). Generally, the distance between two neighboring subunits in contact with the crystal surface should be very small, especially compared to the distance between two neighboring adsorbed small molecule additives at low concentration, and may be even smaller than the critical value r c (12).…”
Section: Analysis On the Effects Of Polymers On Crystallization And Dmentioning
confidence: 98%
“…After single acetaminophen crystals were prepared, the acetaminophen (010) face was acquired by cleaving single acetaminophen crystal and confirmed by X-ray powder diffraction (20). After one confirmed single crystal was mounted onto one AFM sample disk, the a-axis and c-axis directions were determined by observing the crystal two-dimension morphology.…”
Section: Observation Of Etching Patternsmentioning
confidence: 99%
See 1 more Smart Citation